Low carbohydrate intake correlates with trends of insulin resistance and metabolic acidosis in healthy lean individuals - Al-Reshed, Fatema; Sindhu, Sardar; Al Madhoun, Ashraf; Bahman, Fatemah; AlSaeed, Halemah; Akhter, Nadeem; Malik, Md. Zubbair; Alzaid, Fawaz; Al-Mulla, Fahd; Ahmad, Rasheed (Frontiers in Public Health, 2023)
Type 2 diabetes mellitus (T2DM) is a major health problem worldwide, characterized by insulin deficiency, uncontrolled hyperglycemia, and loss of beta-cell efficiency. Both obesity and a poor diet are considered major risk factors for triggering insulin resistance syndrome (IRS) and the development of T2DM. Due to the impact of low carbohydrate diets, such as the keto diet and the Atkins diet, on weight loss in obese individuals, lower carbohydrate diets have become an effective strategy for a healthy lifestyle. However, the impact of the ketogenic diet on insulin resistance syndrome (IRS) in healthy, normal-weight individuals is less defined. A total of 120 healthy, normal-weight participants (BMI ≤25 kg/m2) with no history of a major medical condition were recruited for this study. Self-reported dietary intake and objective physical activity measured by accelerometry were tracked for 7 days. Participants were divided into three categories according to their dietary intake of carbohydrates. Blood samples were collected for metabolic markers’ analysis. HOMA of insulin resistance (HOMA-IR) and β-cell function (HOMA-B), along with C-peptide, were used for the evaluation of glucose homeostasis. Low carbohydrate intake (less than 45% of total energy) was found to significantly correlate with dysregulated glucose homeostasis as measured by elevations in HOMA-IR, HOMA-% assessment, and C-peptide levels. Low carbohydrate intake was also found to be coupled with lower serum bicarbonate and serum albumin levels, with an increased anion gap indicating metabolic acidosis. The elevation in C-Peptide under low carbohydrate intake was found to positively correlated with the secretion of IRS-related inflammatory markers including FGF2, IP-10, IL-6, IL-17A and MDC, however, with a negative correlation with IL-3 Overall, the data show for the first time that low carbohydrate intake can lead to dysfunctional glucose homeostasis, increased metabolic acidosis, and triggered T2DM-related inflammation caused by C-peptide elevation in plasma.